Culture Meets Leadership: Boosting Employee Performance Through Satisfaction - Fatahilah, Ahmad; Budiono, Nur Aktif (Asean International Journal of Business, 2025)
Purpose – This study employed a quantitative research, using a skala likert questionnaire administered to a sample of 87 employees at PT. Asiaparts Indotech, South Tangerang. The data were analyzed using Structural Equation Modeling (SEM) to rigorously assess the direct and indirect effects among the variables studied. Methodology/approach – A quantitative research design was adopted, utilizing a structured questionnaire administered to a representative sample of employees. Data were analyzed using Structural Equation Modeling (SEM) to rigorously assess the direct and indirect effects among the studied variables. Findings – The empirical results demonstrate that both transformational leadership and organizational culture exert significant positive influences on sustainable employee performance. Additionally, job satisfaction was found to partially mediate the relationship between transformational leadership, organizational culture, and sustainable performance, highlighting the pivotal role of employee satisfaction in achieving long-term organizational outcomes. The study shows that job satisfaction mediates the impact of leadership and organizational culture on employee performance, emphasizing the need for effective leadership and strong culture to sustain productivity